2022
DOI: 10.3389/frwa.2022.886703
|View full text |Cite
|
Sign up to set email alerts
|

Microplastic occurrence after conventional and nanofiltration processes at drinking water treatment plants: Preliminary results

Abstract: Microplastics (MP) have been detected in almost all matrices, including drinking water, and assessing the contamination of drinking water with this type of pollution is of the utmost sanitary importance. This study aims to evaluate MP contamination of inlet river water and drinking water at three drinking water treatment plants (DWTPs) in the Paris region in France. Each plant performs water treatment processes that are efficient for particulate matter removal such as coagulation-flocculation, sand filtration,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…With pore sizes of about 10 nm, high NP removal efficiencies are expected through such treatment processes. Barbier et al [104] showed, for the first time, that the nanofiltration process is more efficient than conventional methods (coagulation-flocculation, settling, sand filtration, ozonation, GAC filtration, UV treatment, and chlorination) used to remove MPs from DWTPs. Thus, by applying nanofiltration for MP removal from three DWTPs, the authors reported concentrations ranging from 7.4 to 45.0 MPs/L in the inlet water, while these decreased to 0.260 MPs/L in the case of outlet drinking water.…”
Section: Membrane Filtration Processmentioning
confidence: 99%
See 1 more Smart Citation
“…With pore sizes of about 10 nm, high NP removal efficiencies are expected through such treatment processes. Barbier et al [104] showed, for the first time, that the nanofiltration process is more efficient than conventional methods (coagulation-flocculation, settling, sand filtration, ozonation, GAC filtration, UV treatment, and chlorination) used to remove MPs from DWTPs. Thus, by applying nanofiltration for MP removal from three DWTPs, the authors reported concentrations ranging from 7.4 to 45.0 MPs/L in the inlet water, while these decreased to 0.260 MPs/L in the case of outlet drinking water.…”
Section: Membrane Filtration Processmentioning
confidence: 99%
“…Metabolomics is a powerful tool for studying cellular metabolism and can be used to identify changes in metabolite levels in response to exposure to plastic NPs. The authors used pulsedlaser ablation of solid PET films in water to form PET NPs (size distribution in the range of 10 and 80 nm) of similar surface and shape irregularity, broad size distribution, and chemistry to those of particles in the environment [104]. They found a binding capacity of about 3% w/w NPs for PET NPs with levofloxacin, an antibiotic defined as an emerging contaminant in aqueous environments and demonstrated that these nanoclusters are not toxic to heterogeneous human epithelial colorectal adenocarcinoma cells (Caco-2) in the short term, but affect the cells metabolism as a compensatory response to oxidative stress, suggesting long-term risks.…”
Section: Potential Toxicological Effects Of Micro-and Nanoplastics Fr...mentioning
confidence: 99%
“…Furthermore, the General Office of the State Council of China issued the "Action Plan for the Control of New Pollutants" in 2022, which clearly pointed out that MPs, as an emerging pollutant, are in urgent need of environmental risk assessment and pollution control [20]. Recently, attempts have been made to remove microplastics from drinking water using several conventional drinking water treatment technologies, including coagulation, sedimentation, sand filtering, and membrane separation [15,21,22]. However, because of the ambiguous removal mechanism and the constrained technical parameters, the removal of MPs in the drinking water treatment process remains a significant challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Water resources worldwide are becoming increasingly polluted with a variety of chemical compounds of anthropogenic origin, among which pesticides, biocides, pharmaceuticals, personal care products, endocrine disruptors, heavy metals, perfluorinated compounds, or flame retardants are the most commonly described (Liu et al, 2017; Pivokonský et al, 2020; Schriks et al, 2010; Shannon et al, 2008; Ternes et al, 2015). Their effective removal in drinking water treatment depends on the increasingly complex technologies used for this purpose (Barbier et al, 2022; Chu et al, 2022; Moel et al, 2006; Sharifi & Movahedian Attar, 2022). Water producers are obliged to provide safe drinking water and protect public health.…”
Section: Introductionmentioning
confidence: 99%